ANALISIS MOTIVASI KERJA UNTUK MENINGKATKAN KINERJA KARYAWAN PADA BATAVIA COFFEE AND ROASTERY - Sabila, Salsa; Yunanti, Siska (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study aims to analyze work motivation in improving employee performance at Batavia Coffee and Roastery, a local coffee shop competing in the food and beverage (F&B) industry. Work motivation is an important factor in supporting employee productivity and achieving company goals. This research uses a descriptive qualitative method with data collection techniques through observation, in-depth interviews, and documentation involving the owner, assistant, and employees. The results show that employee motivation is influenced by both internal and external factors. Internal factors include the fulfillment of physiological needs, safety, social relationships, recognition, and self-actualization. External factors consist of compensation, work environment, leadership, and reward systems. Based on the preliminary survey, most employees stated that salaries were insufficient to meet living needs, job security was limited, and tasks lacked challenges. These conditions led to decreased enthusiasm, low initiative, and limited creativity. However, the study also found that supportive leadership, harmonious teamwork, and the provision of rewards such as bonuses and praise significantly increased work motivation. This positively affected employee performance, particularly in terms of quantity, quality, discipline, and accuracy of work. In conclusion, work motivation plays an essential role in enhancing employee performance at Batavia Coffee and Roastery. The company should focus more on aspects of compensation, reward systems, and opportunities for self-development so that employee motivation is maintained and has a positive impact on business sustainability